Mosquito density in rural Kerala: a study on the trend of Aedes larval indices over monsoon in a rural area of Thrissur district, India - Vaz, Clint; Harikumar, Anjali; Mundodan, Jenyz M; Rafi, Mohamed; Saju, C. R. (International Journal Of Community Medicine And Public Health, 2019)
Background: Dengue is one of the most rapidly spreading mosquito-borne viral diseases in the world. Aedes aegypti mosquito is the main vector of dengue and Chikungunya. Entomological surveillance on Aedes mosquito has been standardized on different indices like House index, Container index, Breteau index. Larval indices are important predictors of outbreaks and are valuable in taking preventive measures. The objectives of the present study was to study the trend of larval indices over four months in selected wards of Kaiparambu Panchayat, Thrissur, Kerala, India and to identify the major breeding sources. Methods: A series of surveys were conducted from May to August of 2017 in Kaiparambu Panchayat under the field practice area of Amala Institute of Medical Sciences Thrissur. Houses were selected serially from 4, 5 and 6 wards with roughly 120 houses being covered each month. Results: A total of 489 houses were surveyed over 4 months. Overall, positive containers (with larvae) were present in 375 of 4055 potential containers showing a calculated House index (HI) is 44.4%, Container index (CI) is 11.5% and the Breteau Index is 76.7%. All three indices increased from May to June, peaked in July and dropped by August. Plastic containers were the most common source of breeding. Conclusions: The indices indicate risk even in the pre-monsoon season and there is a marked rise during monsoon. Hence, control measures need to be adopted during the pre-monsoon season so as to reduce the impact of the impending outbreak.